Elevated levels of apelin predict favorable clinical course of heart failure in type 2 diabetes mellitus patients - Berezin, A. E.; Fushtei, I. M.; Berezin, A. A.; Березін, Олександр Євгенійович (My University, 2022)
Apelin is a regulatory peptide having positive inotrope and reparative abilities. Type 2 diabetes mellitus (T2DM) is common comorbidity that is associated to occurrence of HF mainly HF with preserved ejection fraction (HFpEF). The discriminative potency of conventional cardiac biomarkers such as natriuretic peptides in HFpEF was found to be sufficiently lower compared to HF with reduced / mildly reduced ejection fraction (HFrEF / HFmrEF). The aim of the study was to investigate whether serum levels of apelin predict HF in patients with T2DM.
Keywords: atrial fibrillation; left ventricular ejection fraction; hemodynamics; echocardiography